2015
DOI: 10.1371/journal.pone.0143008
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Finite Rate of Population Increase for Sharks Based on Vital Parameters

Abstract: The vital parameter data for 62 stocks, covering 38 species, collected from the literature, including parameters of age, growth, and reproduction, were log-transformed and analyzed using multivariate analyses. Three groups were identified and empirical equations were developed for each to describe the relationships between the predicted finite rates of population increase (λ’) and the vital parameters, maximum age (Tmax), age at maturity (Tm), annual fecundity (f/Rc)), size at birth (Lb), size at maturity (Lm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
1
22
1
Order By: Relevance
“…Comparing the results from the current study with previous demographic analysis of the Pacific bigeye thresher population (Cortés, ; Chen &Yuan, 2006; Liu, Chin, Chen & Chang, ) highlights the importance of uncertainty in model structure and life history parameters. Our estimates of finite population growth rate( λ ) are generally similar to those reported by previous studies (Table ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Comparing the results from the current study with previous demographic analysis of the Pacific bigeye thresher population (Cortés, ; Chen &Yuan, 2006; Liu, Chin, Chen & Chang, ) highlights the importance of uncertainty in model structure and life history parameters. Our estimates of finite population growth rate( λ ) are generally similar to those reported by previous studies (Table ).…”
Section: Discussionsupporting
confidence: 64%
“…The results from the demographic model indicated that bigeye threshers can only support very limited fishing mortality; thus, the present findings emphasise the importance of reducing fishing pressure for this species. Moreover, it has been shown that long-lived species with a low rate of natural mortality and low fecundity (like most shark species) cannot sustain high levels of fishing pressure (Chen & Yuan, 2006;Cortés, 2008;Cortés et al, 2010;Liu et al, 2015). Therefore, the present estimate of catch at size could be used to represent the utilisation of bigeye thresher stock in the northeastern Taiwan waters.…”
Section: Scenariomentioning
confidence: 99%
“…3). While our study did not explore the relationship between relative maturation (the α mat /α max ratio) and r max values among species, a negative relationship between relative maturation and intrinsic rate of population increase has been previously pointed out in sharks (Liu et al, 2015) and skates (Barnett et al, 2013).…”
Section: Resultsmentioning
confidence: 82%
“…Ecological and anthropogenic events contribute to changes in the size of natural populations. S. tiburo presents a higher rate of population increase in the estuaries of the Florida Panhandle (Cortés & Parsons, ) than S. lewini (Liu et al ., ; Smith et al ., ), which agrees with their levels of mitochondrial genetic diversity (Castillo‐Olguín et al ., ; Escatel‐Luna et al ., ; Nance et al ., ). In the NMP, S. zygaena has historically been one of two most abundant sphyrnids fished, but there are fewer catch records for this species compared with S. lewini as S. zygaena presents a primarily pelagic distribution while the fisheries in the NMP are mainly coastal, artisanal fishery (Bizzarro et al ., , ; Cartamil et al ., ; Pérez‐Jiménez, ; Saldaña‐Ruiz et al ., ; Smith et al ., ).…”
Section: Discussionmentioning
confidence: 97%